The Luwians of Western Anatolia. - Woudhuizen, Fred.
1 online resource (186 pages)
Keywords: A study focussing on the Luwians of Western Anatolia, the geography of their habitat, and their neighbours and predecessors in the region. A reconstruction of western Luwian history and a sketch of their language is presented, based on linguistic data taken from hieroglyphic inscriptions and cuneiform script.